Computed tomography–based pericoronary adipose tissue attenuation in patients undergoing TAVR: a novel method for risk assessment - Steyer, Alexandra; Mas-Peiro, Silvia; Leistner, David M.; Puntmann, Valentina O.; Nagel, Eike; Dey, Damini; Goeller, Markus; Koch, Vitali; Booz, Christian; Vogl, Thomas J.; Martin, Simon S. (Frontiers in Cardiovascular Medicine, 2023)
Objectives: This study aims to assess pericoronary adipose tissue (PCAT) attenuation surrounding the proximal right coronary artery (RCA) in patients with bystanding aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR). RCA PCAT attenuation is a novel computed tomography (CT)-based marker for the evaluation of coronary inflammation. Coronary artery disease (CAD) in TAVR patients is common and usually evaluated prior to intervention. The most sensible screening method and consequential treatment approach is unclear and a matter of ceaseless discussion, thus interest remains for safe and low-demand predictive markers to identify patients at risk for adverse outcomes post aortic valve replacement. Methods: This single-center retrospective study included patients receiving a standard planning CT scan prior to TAVR. Conventional CAD diagnostic tools such as coronary artery calcium score (CACS) and significant stenosis via invasive coronary angiography (ICA) and coronary computed tomography angiography (CCTA) were determined in addition to RCA PCAT attenuation using semi-automated software. These were assessed for their relationship with major adverse cardiovascular events (MACE) during a 24-month follow-up period. Results: From a total of 62 patients (mean age: 82 ± 6.7 years), 15 (24.2%) patients experienced an event within the observation period, 10 of which were attributed to cardiovascular death. The mean RCA PCAT attenuation was higher in patients enduring MACE than in those without an endpoint (- 69.8 ±7.5 vs. 74.6 ±6.2, P = .02). Using a pre-defined cutoff of > - 70.5HU, 20 patients (32.3%) with high RCA PCAT attenuation could be identified, 9 (45%) of which met the endpoint within two years after TAVR. In a multivariate cox regression model including conventional CAD diagnostic tools, RCA PCAT attenuation prevailed as the only marker with significant association with MACE (P = .02). After dichotomization into a high and low RCA PCAT attenuation group, high attenuation was related to greater risk of MACE (HR: 3.82, P = .011). Conclusion: RCA PCAT attenuation appears to have predictive value also in a setting of concomitant AS in patients receiving TAVR. Identification of patients at risk for MACE was more reliable using RCA PCAT attenuation than conventional CAD diagnostic tools.